Linguistics and New Testament interpretation essays on discourse analysis - Black, David Alan; Wycliffe Bible Translators (Nashville, TN Broadman, 1992)
Includes bibliographical references.
Selected papers from a conference held in 1991, sponsored by Wycliffe Bible Translators
Keywords: Bible. N.T. -- criticism, interpretation, etc; Bible. N.T. -- linguistics